Petrografia, suscetibilidade magnética, geoquímica e geocronologia do Granito Rio Branco - Província Mineral de Carajás, sudeste do Pará - SANTOS, Patrick Araújo dos (2019)
The Paleoproterozoic Rio Branco stock covers an area of ~31 km2 and is intrusive in Archean calc-alkaline foliated biotite-bearing monzogranite of the Canaã dos Carajás region, Carajás Mineral Province. It is constituted by undeformed and isotropic, hololeucocratic syenogranite, showing equigranular texture. The granite is formed essentially by perthite alkali feldspar, quartz, and plagioclase, with additional variable amounts of chloritized biotite. Fluorite, allanite, and zircon are accessory minerals, whereas magnetite, pyrite, and chalcopyrite are scarce. Scanning electron microscopy studies indicate that these rocks also contain Ce-fluocerite, xenotime, and heavy rare earth minerals. Albitization and greisenization are the main alteration processes that affected the granite, being the mineralogy represented by albite, fluorite, topaz, chlorite, muscovite, siderophyllite, and iron oxides. Magnetic susceptibility values vary between 1,3 x 10-5 a 6,9 x 10-4 (SI), which indicate the reduced character of the granite. Geochemistry data on the Rio Branco Granite demonstrate its affinity with reduced A2-type intraplate granite. It is subalkaline, metaluminous to peraluminous and shows high FeOt/(FeOt+MgO). The rare earth element (REE) patterns are flat with little heavy REE fractionation and show accentuated negative Eu anomalies (Eu/Eu*=0,08-0,13). These characteristics are typical of evolved granites, derived from volatile-enriched liquids responsible by the intense subsolidus hydrothermal alteration. The dating of the Rio Branco granite did not give conclusive results, due to the metamictic state of the zircon, but the obtained data, associated with geological evidence, suggest that the granite is Paleoproterozoic. The comparison between the Rio Branco granite and Paleoproterozoic A-type suites of the Carajás Province suggests that the Rio Branco granite presents greater affinity with the Velho Guilherme suite and, in lesser degree, with the Serra dos Carajás suite. On the other hand, it is clearly distinct of the oxidized A-type granites of the Jamon Suite. Two minor occurrences of isotropic granites located near the Serra Dourada village and to the north of the Planalto stock are also of syenogranitic composition.